THE MEDIATING EFFECTS OF LEAN LEADERSHIP ON THE INFLUENCE OF LEAN MANAGEMENT AND GEMBA PRACTICES TOWARDS SUSTAINABILITY PERFORMANCE OF NATIONAL BANK OF OMAN - Ali Suleiman Ali Al Rusheidi; Kamisah Supian (International Journal of Accounting, Finance and Business, 2022)
The objectives of paper is to investigate the mediating effect of lean leadership on the influence of lean management and Gemba practices towards sustainable performance in the National Bank of Oman. A total of 129 managers and employees in the Oman National Bank has been selected through simple random sampling technique. The Partial Least Squares - Structural Equations Method (PLS-SEM) technique was applied to measure the model by using Smart PLS software. The finding reveals that lean leadership has an indirect-only mediation role in the association between lean management practices towards sustainability performance. This result indicates that the implementation of lean management practices supported by the lean leadership attributes by the managers may ends up contributes significantly to sustainability performance of the Oman National Bank. Besides, the finding also support the Contingency Theory whereby the impact of lean management practices on sustainability performance is mediated by contextual variable, namely as lean leadership. Therefore, this study recommends that the leaders at the National Bank of Oman should be able to modify their frequent command and control style towards lean leadership by enhancing employees’ engagement and self-development while implementing quality improvement management strategies.